Validity of Historical Learning Based on Islamic History (Psi-Bk) As a radicalism date for Radicalism in High Education - Heri Effendi; Siti Aisyah; Muspardi; Muslim (ICHELSS: International Conference on Humanities, Education, Law, and Social Sciences, 2021)
The phenomenon of radicalism in Indonesia is still an interesting topic and continues to warm up today. The results of research on campus Islam involving 2,466 samples of students from various well-known universities in Indonesia. Students tended to support sweeping by arguing that theactivity sweeping was part of an order, the security forces were unable to enforce the law and for reasons of moral decadence. This study aims to develop a model of Islamic History Learning Based on Diversity (PSI-BK) as a Counteracting Force of Radialism in Higher Education. To achieve the goals and targets described in this study, Sugiyono's model development research was carried out, by taking steps: (1) potential and problems), (2) data collection, (3) product design, (4) design validation, ( 5) improve design, (6) product trials, (7) product revisions, (8) product trials, (9) product revisions, (10) mass product manufacturing. The product of the PSI-BK model was then validated by 8 experts as validators through themechanism validated focus group discussion (FGD)including (1) the content aspect scored 93.75 very valid categories, (2) the linguistic aspect scored an average of 88.69 categories is very valid, (3) the graphic aspect gets an average score of 87.27 very valid categories, (4) the model design aspect gets an average score of 91.25 categories is very valid, the result is an average value the whole of the validators is 93.9 very valid categories.